An observational study of the blood use in combat casualties of the French Armed Forces, 2013–2021. Issue 1 (25th November 2022) - Py, Nicolas; Pons, Sandrine; Boye, Matthieu; Martinez, Thibault; Ausset, Sylvain; Martinaud, Christophe; Pasquier, Pierre
Abstract: Background: The French Armed Forces conduct asymmetric warfare in the Sahara‐Sahel Strip. Casualties are treated with damage control resuscitation to the extent possible. Questions remain about the feasibility and sustainability of using blood for wider use in austere environments. Methods: We performed a retrospective analysis of all French military trauma patients transfused after injury in overseas military operations in Sahel‐Saharan Strip, from the point of injury, until day 7, between January 11, 2013 to December 31, 2021. Results: Forty‐five patients were transfused. Twenty‐three (51%) of them required four red blood cells units (RBC) or more in the first 24H defining a severe hemorrhage. The median blood product consumption within the first 48 h, was 8 (IQR [3; 18]) units of blood products (BP) for all study population but up to 17 units (IQR [10; 27.5]) for the trauma patients with severe hemorrhage. Transfusion started at prehospital stage for 20 patients (45%) and included several blood products: French lyophilized plasma, RBCs, and whole blood. Patients with severe hemorrhage required a median of 2 [IQR 0; 34] further units of BP from day 3 to day 7 after injury. Eight patients died in theater, 4 with severe hemorrhage and these 4 used an average of 12 products at Role 1 and 2. Conclusion: The transfusion needs were predominant in the first 48 h after the injury but also continued throughout the first week for the most severe trauma patients. Importantly, our study involved a low‐intensity conflict, with a small number of injured combatants.